Perceived wildfire risk and past experiences with wildfire smoke influence public support for prescribed burning in the western conterminous United States - Christopher J Rogers; Celeste Beck; Rima Habre; Jo Kay Ghosh (BMC Public Health)
Abstract Background Prescribed burning is an important fuel management tool to prevent severe wildfires. There is a pressing need to increase its application to reduce dry fuels in the western United States, a region that has experienced many damaging wildfires. Public support for this practice is tempered by concern around smoke impacts and escape risks. This study aims to understand how recent experiences with wildfire smoke and perceived risk of smoke events affect public support for prescribed burning. Methods Data were from the May 2023 Household Emergency Preparedness Survey, an online panel survey of 1,727 adults in 12 western conterminous states, applying survey weights to reflect the underlying population demographics. In weighted logistic regression models, we evaluated associations between predictor variables (past experiences with smoke, wildfire risk perception) and support for prescribed burns in general or near a respondent’s neighborhood, adjusting for age, race/ethnicity, gender, education, household income, and wildland urban interface status. Mediation models were used to assess whether perceived risk of smoke exposure mediates the relationship between recent smoke experience and support for prescribed burning. Results Approximately two-thirds of the population supported prescribed burning in general, and more than half supported prescribed burning near their neighborhood. 44% reported experiencing a smoke event in the past 3 years, which increased the odds of support for prescribed burning in general (OR = 2.03, 95%CI 1.51–2.74) and near their neighborhood (OR = 1.59, 95% CI 1.20–2.09). High perceived risk of future smoke impacts was associated with support for prescribed burns in general (adjusted OR = 1.66, 95% CI = 1.15–2.39) and near their residence (adjusted OR = 1.72, 95%CI = 1.23–2.39). Although only trending towards significance, perceived future risk mediated 16.9% (p = 0.066) of the association between recent smoke experience and support for prescribed burning nearby. Among those who experienced recent smoke events, reporting high degrees of overall smoke impacts or outdoor air quality impacts were positively associated with support for prescribed burns. Conclusions Recent experience with wildfire smoke and perceived future risk are strongly associated with support for prescribed burns. Educational campaigns can apply these findings to improve public support toward prescribed fire activities and funding to reduce wildfire risks and protect public health.